The Contribution of The Intensity of Playing Online Games and The Supervision of Both Working Parents Towards Children’s Religiosity - Prasetiya, Benny; Hasan, Misbahul; Sitaresmi, Pratiwi Dwi Warih; Dheasari, Agustiarini Eka (Jurnal Pendidikan Agama Islam, 2020)
This research aims to determine the contribution of the intensity of playing online games and the supervision of both working parents towards the child's religiosity in MAN 2 Probolinggo. There were 100 students of MAN 2 Probolinggo used as the samples. This study used purposive sampling technique with some criteria. In testing the hypothesis, the researcher utilized regression analysis techniques. The method of data collection was through questionnaires given to respondents. Based on the results of data analysis using logistic regression, it can be seen that the partial influence of the intensity of playing online games showed significance value of 0.000, which was smaller than 0.05, and the supervision of both working parents generated its significance value of 0.000 (smaller than 0.05) towards the religiosity of the child. These results indicate that there is influence of the intensity of playing online games and the supervision of both working parents towards the religiosity of the child in MAN 2 Probolinggo.